Pelatihan Pendidikan Keluarga Ramah Anak dalam mewujudkan Kelurahan Layak Anak - Sowiyah sowiyah; Riswanti Rini; Sofyan Musyabiq Wijaya (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2022)
The specific objectives to be achieved in this activity are to train participants to understand the convention on the rights of the child through a sift-friendly family (KRA) in creating Child Friendly Villages and increase understanding of the four principles of the convention on children's rights; non-discrimination, the best interests of the child, growth and development, and child participation. The strategy used to achieve this goal is in accordance with the mission contained in the vision of Metro City regarding the prevention of violence against women and violence against children. This activity was carried out in order to provide reinforcement and provision for PKK members and children's forums in the Ganjar Agung family, West Metro District, Metro City. Ganjar Agung Urban Village, which has launched a Women-Friendly and Caring for Children Village (KRPPA) which was launched on November 28, 2021 by the Minister of Women's Empowerment and Child Protection of the Republic of Indonesia. Based on these data, it is very necessary to hold training for the community and children's forums in the Ganjar Agung Village. The methods used in this activity are outreach, training, assignments, practice, group discussions, and mentoring. This activity will be held at the Ganjar Agung Village Office, West Metro District.